Multi-dimensional Sources Apportionment of PM2.5 in Zhongyuan Urban Agglomeration Based on the CAMx Mode - Jinyu He; Wenbo Xue; Li Yan; Xurong Shi; Yanchao Wang; Yu Lei; Yixuan Zheng; Yu Zhang (Aerosol and Air Quality Research)
Abstract Based on the comprehensive air quality model with extensions (CAMx), the quantitative simulation was conducted on the transport impact of PM2.5 between Zhongyuan Urban Agglomeration and surrounding cities in 2017, and the contribution of 5 major emission sectors to urban PM2.5 concentrations, namely the sector of power, industry, household, transportation and agriculture. A two-dimensional cross matrix was established for 18 cities and major emission sectors in Zhongyuan Urban Agglomeration (hereafter referred as the Urban Agglomeration). The results showed that: On an annual average scale, among the transport contribution to the 18 cities of the Urban Agglomeration, 37.8%–57.8% was from local sources, 6.2%–26.3% from the transport within the Urban Agglomeration, and 5.9%–17.4% from other cities nearby; In terms of sectors contribution, industrial sources contributed the most to the annual average concentration of PM2.5 (12.7%–33.0%) in the Urban Agglomeration, followed by household, transportation and agriculture sources. Household source emissions contributed the most in winter. PM2.5 concentrations in Shangqiu, Puyang and Zhoukou affected by household sources emissions exceeding 30% in winter.